1998
DOI: 10.1037/10301-000
|View full text |Cite
|
Sign up to set email alerts
|

Investigative interviews of children: A guide for helping professionals.

Abstract: L nterviewing children as part of an investigation is an area ripe with both sensitivity and with controversy. Professional interviewers are coming under increasing scrutiny, and their techniques must pass rigorous review by outside agencies, at the same time serving the needs of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
481
0
29

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 451 publications
(517 citation statements)
references
References 306 publications
7
481
0
29
Order By: Relevance
“…In both studies, details elicited using suggestive and option-posing prompts were most likely to be contradicted by the same informants, whereas those elicited using open-ended invitations were never contradicted themselves and never contradicted earlier reported details. These findings add support to recommendations by professional and expert groups emphasizing that forensic interviewers should rely as much as possible on open-ended questions when obtaining information from alleged victims of child sexual abuse and take special care to avoid risky questions when interviewing young children (American Professional Society on the Abuse of Children, 1990Children, , 1997Home Office & Department of Health, 1992, 2002Jones, 1992Jones, , 2003Lamb 1994;Poole & Lamb, 1998).…”
Section: Memorysupporting
confidence: 48%
See 2 more Smart Citations
“…In both studies, details elicited using suggestive and option-posing prompts were most likely to be contradicted by the same informants, whereas those elicited using open-ended invitations were never contradicted themselves and never contradicted earlier reported details. These findings add support to recommendations by professional and expert groups emphasizing that forensic interviewers should rely as much as possible on open-ended questions when obtaining information from alleged victims of child sexual abuse and take special care to avoid risky questions when interviewing young children (American Professional Society on the Abuse of Children, 1990Children, , 1997Home Office & Department of Health, 1992, 2002Jones, 1992Jones, , 2003Lamb 1994;Poole & Lamb, 1998).…”
Section: Memorysupporting
confidence: 48%
“…In general, students of episodic or autobiographical memory found that, as children grow older, the length, informativeness, and complexity of their recall increase (see Fivush, 1997Fivush, , 1998Poole & Lamb, 1998;Saywitz & Camparo, 1998;Schneider & Pressley, 1997, for reviews) but that even very young children can provide temporally organized and coherent narratives. These accounts are generally quite accurate, although young children tend to provide briefer free narratives than do older children and adults (e.g.…”
Section: Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Direct questions and non-verbal props (such as in the provision of dolls and toys) have been found to increase the child's level of recall above that which is obtained from free recall only (e.g., see Poole & Lamb, 1998;Salmon, Bidrose & Pipe, 1995), but both methods are Drawings As Memory Aids 3 also prone to eliciting more inaccurate information (Brady, Poole, Warren & Jones, 1999;Peterson & Bell, 1996;Salmon et al, 1995). An inherent problem with asking a child direct questions about an experienced event is that such questions may lead him or her to an inaccurate answer the child thinks the interviewer wants or expects.…”
Section: Introductionmentioning
confidence: 99%
“…After the initial survey, for example, new studies were conducted on such topics as child witnesses (Ceci & Brack, 1995;Poole & Lamb, 1998), repressed and/or false memories of trauma (Loftus, 1993;Pezdek & Banks, 1996;Read & Lindsay, 1997), the effects of alcohol (Yuille & Tollestrup, 1990), the processes by which eyewitnesses make identifications (Dunning & Stern, 1994;Sporer, 1993), sequential versus simultaneous presentations of photographic arrays and lineups (R. C. L. Lindsay, Lea, & Fulford, 1991;Wells, 1993), the malleability of confidence and other retrospective reports of the eyewitnessing experience (Luus & Wells, 1994;Shaw, 1996;Wells & Bradfield, 1998, 1999, factors that moderate the correlation of accuracy and confidence (Kassin, Rigby, & Castillo, 1991;D. S. Lindsay, Read, & Sharma, 1999;Robinson & Johnson, 1999;Sporer, Penrod, Read, & Cutler, 1995), and the commonsense assumptions about eyewitnesses held by laypersons and members of the legal profession (Devenport, Penrod, & Cutler, 1997;Kassin & Barndollar, 1992;Stinson, Devenport, Cutler, & Kravitz, 1996.…”
mentioning
confidence: 99%